Parameters describing the variable adsorption capacity of the ground as auxiliary tools in determining changes of groundwater quality (in saturated zone) - Aniszewski, Andrzej (Instal, 2019)
An important issue in the transport of pollutants in the ground is the demonstration of the impact the time-dependent adsorption capacity of this ground on the change in the quality of groundwater (in a saturated zone). At work both for the selected ground and pollutants flowing in it, there is a tendency change of the adsorption capacity of this ground based on the adopted parameters characterizing this capacity (Ra, ux/Ra, ΔC*max). The analysis of the numerical values of these parameters showed both a declining tendency in time of the adsorption capacity of the analyzed ground as well as in a gradual increase contamination of groundwater. Therefore, the conclusions of these research can be very useful in practice, when using groundwater resources for various purposes and when simultaneously the purity of these waters decreases in time.
Keywords: advection; dispersion; non-linear adsorption; adsorption capacity parameters; transport model